Agarā janapada kā rājanaitika itihāsa : svatantratā saṅgrāmoṃ kī amaragāthā - Śukla, Cintāmaṇi, 1910- (Śuklā Prakāśana, 1980)
On the role of Agra District, Uttar Pradesh, in the Indian freedom struggle; includes a political history and who's who of the district.